Pengaruh Penerapan Model Pembelajaran Make A Match Terhadap Minat Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Pagaran Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024. - Menta Uli Purba; Albiner Siagian; Simion D. Harianja; Johari Manik; Taripar A. Samosir (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Learning models greatly determine the success of learning, including students' interest in learning. This research aims to determine the effect of implementing the Make A Match learning model on interest in studying Christian Religious Education and Characteristics of class XI students at SMA Negeri 1 Pagaran, North Tapanuli Regency for the 2023/2024 academic year. The method used in this research is a quantitative method, a type of pre-experimental approach with a